2019
DOI: 10.3390/e21010026
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Frontal Cortex fNIRS Can Support Alzheimer Disease Diagnosis in Memory and Visuo-Spatial Tests

Abstract: Decline in visuo-spatial skills and memory failures are considered symptoms of Alzheimer’s Disease (AD) and they can be assessed at early stages employing clinical tests. However, performance in a single test is generally not indicative of AD. Functional neuroimaging, such as functional Near Infrared Spectroscopy (fNIRS), may be employed during these tests in an ecological setting to support diagnosis. Indeed, neuroimaging should not alter clinical practice allowing free doctor-patient interaction. However, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 63 publications
(78 reference statements)
1
33
0
Order By: Relevance
“…An entropy-based fNIRS signal complexity analysis demonstrated that the digit span task (DST) could help classify AD. 244 A time-series analysis revealed that the reduction or decline in HbO levels becomes steeper when the intensity of AD progresses. 236…”
Section: Digit Span Testmentioning
confidence: 99%
See 2 more Smart Citations
“…An entropy-based fNIRS signal complexity analysis demonstrated that the digit span task (DST) could help classify AD. 244 A time-series analysis revealed that the reduction or decline in HbO levels becomes steeper when the intensity of AD progresses. 236…”
Section: Digit Span Testmentioning
confidence: 99%
“…The clock drawing test (CDT) scores can adequately be used to di®erentiate between healthy individuals and AD patients; however, the entropy analysis conducted on fNIRS recordings while the subjects were performing the CDT resulted in signi¯cant di®erences between the results of AD patients and healthy subjects. 244…”
Section: Clock Drawing Testmentioning
confidence: 99%
See 1 more Smart Citation
“…For an early Alzheimer’s disease (AD) diagnosis, Perpetuini et al used sample entropy and the MSE of functional near infrared spectroscopy (fNIRS) in the frontal cortex of early AD and healthy controls during three tests that were used to assess visuo-spatial and short-term-memory abilities [ 19 ]. A multivariate analysis revealed promising results (good specificity and sensitivity) in the capabilities of fNIRS and complexity for an early diagnosis.…”
Section: Applications Of Existing Entropy-based Measuresmentioning
confidence: 99%
“…Furthermore, Jin et al investigated permutation entropy to analyze differences in experts and novices solving science problems [ 20 ]. Studying frontal cortex fNIRS signals, SampEn was suggested as a biomarker for Alzheimer’s disease diagnosis [ 21 , 22 , 23 ], and Angsuwatanakul et al [ 24 ] investigated the effects of working memory experiments on SampEn estimated from fNIRS series. Also, though applied as an information theoretic approach to investigate linear effects in fNIRS rather than analyze topological entropy in phase space, differential entropy has been investigated in Keshmeri et al as a biomarker that preserves variational information in the assessment of working memory [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%